Gastric Ulcers in Middle-Aged Rats: The Healing Effect of Essential Oil from Citrus aurantium L. (Rutaceae) - Polo, C. M.; Moraes, T. M.; Pellizzon, C. H. [UNESP]; Marques, M. O.; Rocha, L. R. M.; Hiruma-Lima, Clélia Akiko [UNESP] (Hindawi Publishing Corporation, 2012)
The elderly population has experienced increased life expectancy as well as the increased incidence of gastric ulcers. The peels of fruits from Citrus aurantium L., popularly known in Brazil as orange bitter, are commonly used asatea form for the treatment of gastrointestinal tract disorders, such as ulcer and gastritis. We evaluated the healing effects of essential oil from the peels of Citrus aurantium fruits (OEC) on gastric ulcers in middle-aged rats. We examined the effects of a 14-day chronic OEC treatment on gastric mucosa in middle-aged male Wistar rats that were given acetic-acid-induced gastric lesions by morphometric and immunohistological analyses. Oral OEC treatment significantly reduced the lesion area (76%) within the gastric mucosa and significantly increased (P < .05) the height of regenerated mucosa (59%) when compared to the negative control group. Immunohistochemical analysis of the molecular markers such as COX-2, HSP-70, VEGF, and PCNA in the gastric mucosa confirmed that OEC treatment induced healing effects by increasing the number of new blood vessels and by augmenting gastric mucus in the mucosa glands. These results suggest that the oil from Citrus aurantium effectively heals gastric ulcers in middle-aged animals; however, safe use of OEC demands special care and precautions.